Phenomenological Study Of Borrower Peer To Peer Lending Students at UIN SYAHADA Padangsidimpuan - Hutagalung, Muhammad Wandisyah R.; Siregar, Erpiana; Pohan, Zulhedly (Journal of Islamic Financial Technology, 2022)
The emergence of the phenomenon of students becoming peer to peer lending borrowers who think that peer to peer lending is a solution for students who cannot access banking to be able to receive loans both to meet needs and capital assistance to start a business. Thus encouraging this research to be aimed at describing the phenomena that exist in the field so that the reasons, experiences and meanings and contents can be interpreted more deeply for UIN SYAHADA Padangsidimpuan students who become peer to peer lending borrowers. This study uses a qualitative descriptive research method with a phenomenological paradigm. Sources of data used in this study is primary data which in data collection is done by in-depth interviews, observation, and documentation. The results of the study found that the reasons for students to become peer to peer lending borrowers were driven by rational factors and emotional factors, and the student's experience while being a peer to peer lending borrower consisted of pleasant experiences and unpleasant experiences, then meaning that students became peer to peer lending borrowers, namely economic meaning The meaning is constructed based on what has been seen, heard, and felt through his experience as a borrower.